Natural products targeting human lactate dehydrogenases for cancer therapy: A mini review - Yao, Huankai; Yang, Feng; Li, Yan (Frontiers in Chemistry, 2022)
Reprogramming cancer metabolism has become the hallmark of cancer progression. As the key enzyme catalyzing the conversion of pyruvate to lactate in aerobic glycolysis of cancer cells, human lactate dehydrogenase (LDH) has been the promising target in the discovery of anticancer agents. Natural products are the important source of new drugs. Up to now, some natural compounds have been reported with the activity targeting LDH. To give more information for the development of LDH inhibitors and application of natural products, herein, we reviewed the natural compounds with inhibition of LDH from diverse structures and discussed future direction of discovery of natural LDH inhibitors for cancer therapy.